2008
DOI: 10.1007/s10195-008-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

How do porosity-inducing techniques affect antibiotic elution from bone cement? An in vitro comparison between hydrogen peroxide and a mechanical mixer

Abstract: BackgroundIncreasing the porosity of an antibiotic-loaded cement spacer increases the antibiotic elution, but the correlation between porosity and antibiotic elution is not well documented. The purposes of this study was to attempt new porosity-increasing methods and to investigate the correlation between antibiotic elution and both total and surface porosity.Materials and methodsFive types of antibiotic-loaded bone cement (ALBC) using 2 g cefazolin and 40 g cement were prepared. Other than manual mixing, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Therefore, bone cement that is prepared by hand mixing can exhibit greater antibiotic elution. Many studies have used porogens to increase the porosity of bone cement and antibiotic elution [7][8][9][10][11][12][13][14]. McLaren et al reported that the elution of antibiotic from ALBC can be increased via the use of space fillers such as xylitol, glycine, sucrose, and erythritol [12,13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, bone cement that is prepared by hand mixing can exhibit greater antibiotic elution. Many studies have used porogens to increase the porosity of bone cement and antibiotic elution [7][8][9][10][11][12][13][14]. McLaren et al reported that the elution of antibiotic from ALBC can be increased via the use of space fillers such as xylitol, glycine, sucrose, and erythritol [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have reported that increasing the porosity of ALBC can increase antibiotic elution [7,8]. Therefore, dextran [9], hydrogen peroxide (H 2 O 2 ) [10], calcium sulfate (CaSO 4 ) [11], sucrose [12], xylitol [12], and glycine [13] have been used as porogens or space fillers to obtain more porous ALBC. Additionally, the porosity of PMMA can be increased up to 10% via the use of high-speed of hand mixing [14,15].…”
mentioning
confidence: 99%
“…Palacos is known to exhibit more efficient antibiotics elution compared to other cement types. [7,9,[26][27][28] Tabromycin and vancomycin release is documented to be significantly higher with Palacos compared to CMW 1 and CMW 3. [27] There is no such established difference between Simplex P and CMW 3.…”
Section: Discussionmentioning
confidence: 99%
“…the type of bone cement used, the choice of drug [13,14,15,16], the form of drug (e.g. powder vs. crystalline) [17,18], the drug’s chemical compatibility with the bone cement, the optimal initial amount of the chemotherapy drug added, changes in the mechanical property of the bone cement, the optimal mixing method [19], etc. In general, drug elution from bone cements is either incomplete or not ideal.…”
Section: Discussionmentioning
confidence: 99%